2016
DOI: 10.17557/tjfc.56268
|View full text |Cite
|
Sign up to set email alerts
|

VARIATIONS IN THE AGRONOMIC AND QUALITY CHARACTERISTICS OF DOMESTIC AND FOREIGN SAFFLOWER (Carthamus tinctorius L.) GENOTYPES

Abstract: The present study was carried out to determine the agronomic and quality characteristics of domestic and foreign safflower (Carthamus tinctorius L.) genotypes in the 2011-2012 growing season in Isparta. In the study, 39 safflower genotypes were used as the plant material. The highest 1000 seed weight and hull content were detected in Ziyang. Arizona SC III was determined as the genotype with the lowest 1000 seed weight, hull content, seed yield, and oil yield. The highest seed yield was recorded in UC-1 (215.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 13 publications
3
27
2
Order By: Relevance
“…In our study, the differences of hull content between the years may be slightly due to environmental impact. In other studies, similar results were obtained for hull content in safflower (Adali and Ozturk, 2016;Erbas et al, 2016). One of the most important goals in safflower breeding is to increase the oil content and to reach the optimum level with seed and oil yield.…”
Section: Oil Contentsupporting
confidence: 77%
See 2 more Smart Citations
“…In our study, the differences of hull content between the years may be slightly due to environmental impact. In other studies, similar results were obtained for hull content in safflower (Adali and Ozturk, 2016;Erbas et al, 2016). One of the most important goals in safflower breeding is to increase the oil content and to reach the optimum level with seed and oil yield.…”
Section: Oil Contentsupporting
confidence: 77%
“…It has been reported that seed yield varies between 84.9-163.0 kg da -1 in F5 lines derived from crossing Dincer 5-118 × Remzibey-05 safflower varieties (Erbas and Baydar, 2007); 119.5-460.7 kg da -1 in F1 population, 22.7-635.6 kg da -1 in F2 population (Erbas, 2012), 26.0-353.0 kg da -1 in F3 population and 74.5-225.3 kg da -1 in F4 population (Baydar and Erbas, 2014) derived from crossing Dincer 5-118 × Montola 2000 safflower varieties. On the other hand, Erbas and Baydar (2011) and Erbas et al (2016) reported that seed yield of safflower ranged between 79.7-190.7 kg da -1 in 9 genotypes and 15.2-215.9 kg da -1 in 39 genotypes, respectively.…”
Section: Oil Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…5(7), 926-934 927 of the world (Amini et al, 2007). In comparison with other oilseed crops, safflower is characterized by high adaptation ability in regions where winter months are cool and summer months are arid (Erbas et al, 2016).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…These genotypes were grown in a trial area located at the Department of Field Crops, Faculty of Agriculture, Isparta University of Applied Sciences, Isparta (longitude 30º33' E, latitude 37°47' N, elevation 997 m) under the soil and climatic conditions in 2016. The soil properties of the trial area were assessed according to the method proposed by Rowell (1996) and reported based on the results in a previous study (Erbas et al, 2016). The experiments were not irrigated.…”
Section: Plant Materialsmentioning
confidence: 99%